Profil Berpikir Kritis Siswa melalui EDUSAN sebagai Aplikasi Mobile Learning dalam Pembelajaran IPA - Hilman Yusri; Galih Rohmansya Dirasta; Insih Wilujeng; Suyanta; Sri Rejeki Dwi Astuti (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking skills are still infrequently tested in science classes. This study aims to identify students' thinking skills in integrated science learning with subject temperature and conversion. This type of research uses descriptive quantitativeâ€”data sampling using a purposive sampling technique. The subjects of this study were 30 students of class VII SMP Negeri 2 Mlati, Sleman, DIY. The instrument used to identify students' critical thinking skills is within the form of 10 multiple choice tests, with indicators of critical thinking skills consisting of (1) categorizing, (2) concluding deductively and inductively, (3) stating the results, (4) providing solutions and (5) explaining reasons. Data analysis techniques were processed with descriptive statistical data and analysis of each item in critical thinking indicators based on the multiple-choice test results. The results showed that the overall critical thinking skill was 79,33% in the high category. Among the indicators measured, the "categorizing" indicator has the highest percentage, while the â€œproviding solutionsâ€ indicator has the lowest percentage. Integrating designs and strategies in further learning media needs to increase student learning activities.